2004
DOI: 10.3748/wjg.v10.i2.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofHelicobacter pyloriinfection on expressions of Bcl-2 family members in gastric adenocarcinoma

Abstract: AIM:To investigate the effect of Helicobacter pylori (H pylori) infection on the expressions of Bcl-2 family members in gastric adenocarcinoma. METHODS:Gastric adenocarcinoma and resection margin tissues of 95 patients were studied. Semi-quantitative RT-PCR was used to measure Bid, Bax and Bcl-2 mRNA expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Bcl-2 regulates apoptotic processes, and can lead to apoptotic resistance when highly expressed. This protein has been shown to be up-regulated during H. pylori infection with cag ϩ strains (52) and H. pylori-associated gastric cancers (38,39). In this study, Bcl-2 levels were expressed at much higher levels in GECs with wild-type strains than with CagA-deficient strains.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Bcl-2 regulates apoptotic processes, and can lead to apoptotic resistance when highly expressed. This protein has been shown to be up-regulated during H. pylori infection with cag ϩ strains (52) and H. pylori-associated gastric cancers (38,39). In this study, Bcl-2 levels were expressed at much higher levels in GECs with wild-type strains than with CagA-deficient strains.…”
Section: Discussionmentioning
confidence: 57%
“…Because Bcl-2 expression is up-regulated during H. pylori infection and gastric atrophy and cancer (38,39), and down-regulated in apoptotic cells (40), the expression of Bcl-2 was investigated during infection with H. pylori and upon pretreatment with rMIF. Flow cytometric analysis revealed that Bcl-2 expression is induced in GECs upon exposure to H. pylori, but is decreased when cells were exposed to CagA-deficient strains in comparison to wild-type strains (Fig.…”
Section: H Pylori-induced Mif Induces Bcl-2 Expressionmentioning
confidence: 99%
“…The biological significance between H pylori and c-Myc is still not understood. A study from Zang et al [38] has linked the c-Myc expression with cell proliferation while a study from Yang et al [40] on a gastric carcinoma cell line has pointed to a relationship with apoptosis. On the other hand, Kim et al [42] have shown a decrease of c-Myc expression after H pylori eradication, but not in its mRNA level, showing the complexity of this process.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, the expression of c-Myc was higher in the g roups without EBV infection indicating a relationship of c-Myc with gastric carcinogenesis but not with EBV infection [41] . Additionally, some studies point to the involvement of H pylori with c-Myc [38,41] . The biological significance between H pylori and c-Myc is still not understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation